Cryo-imaging of Stem Cell Biodistribution in Mouse Model of Graft-Versus-Host-Disease - Patiwet Wuttisarnwattana (2020)
© 2020, Biomedical Engineering Society. We demonstrated the use of multispectral cryo-imaging and software to analyze human mesenchymal stromal cells (hMSCs) biodistribution in mouse models of graft-versus-host-disease (GVHD) following allogeneic bone marrow transplantation (BMT). We injected quantum dot labeled MSCs via tail vein to mice receiving BMT and analyzed hMSC biodistribution in major organs (e.g. lung, liver, spleen, kidneys and bone marrow). We compared the biodistribution of hMSCs in mice following allogeneic BMT recipients (with GVHD) to the biodistribution following syngeneic BMT (without GVHD). Cryo-imaging system revealed cellular biodistribution and redistribution patterns in the animal model. We initially found clusters of cells in the lung that eventually dissociated to single cells and redistributed to other organs within 72 h. The in vivo half-life of the exogenous MSCs was about 21 h. We found that the biodistribution of stromal cells was not related to blood flow, rather cells preferentially homed to specific organs. In conclusion, cryo-imaging was suitable for analyzing the cellular biodistribution. It could provide capabilities of visualizing cells anywhere in the mouse model with single cell sensitivity. By characterizing the biodistribution and anatomical specificity of a therapeutic cellular product, we believe that cryo-imaging can play an important role in the advancement of stem and stromal cell therapies and regenerative medicine.